Statin utilization and its predictors for the primary prevention of cardiovascular disease among type 2 diabetic patients in a resource-limited setting - Dhaba, Feyisa Assefa; Alemu, Wubshet Abraham; Kitila, Firaol Lamessa; Tolla, Koricho Simie; Alene, Astarekew; Wendimagegn, Zeru Seyoum; Getahun, Kedir Ali; Yesuf, Hassen Ahmed; Woldeyes, Surafel Mekasha (Frontiers in Endocrinology, 2025)
BackgroundCardiovascular disease (CVD) is a major cause of mortality in patients with type 2 diabetes mellitus (T2DM). Statins are essential for the primary prevention of CVD in this high-risk group. Despite guideline recommendations, statin use remains suboptimal in clinical practice. Assessing statin utilization and identifying factors influencing their prescription are vital for enhancing evidence-based care, especially in resource-limited settings. Therefore, this study aimed to evaluate statin use and its predictors for primary CVD prevention among diabetic patients at Arsi Teaching and Referral Hospital in 2023.MethodsA hospital-based cross-sectional study was carried out among 351 diabetic patients at Arsi Teaching and Referral Hospital (ARTH) between February and September 2022. Participants were selected using a systematic random sampling method. Data were collected through a pretested, interviewer-administered structured questionnaire and a checklist. Trained nurses from the diabetic clinic conducted data collection. The collected data were initially entered into Epi Data version 7.2, then exported to SPSS version 26 (IBM, USA) for analysis. The association between statin use and potential predictors was examined using odds ratios (ORs) with 95% confidence intervals (CIs). Variables with a p-value below 0.05 in the multivariable logistic regression were considered statistically significant.ResultsThe prevalence of statin utilization for the primary prevention of CVD among type 2 diabetic patients on follow-up at Asella Teaching Hospital was 189 [(53.8%, 95% CI: 48.6%, 59.0%)]. The most commonly prescribed statin was atorvastatin, followed by simvastatin. The probability of statin use was greater in participants with hypertension [AOR=4.8, 95% CI (2.0-11.5)], dyslipidemia [AOR=10.5, 95% CI (2.0-11.5)], and uncontrolled glycemic control [AOR=8.0,95% CI (3.8-17.7)].ConclusionsSuboptimal statin utilization (53.8%) for primary CVD prevention in type 2 diabetes was observed, with utilization heavily influenced by comorbidities. Urgent quality improvement initiatives are needed to ensure statin access aligns with guideline recommendations for patients with hypertension, dyslipidemia, and poor glycemic control in the study area.